2021
DOI: 10.3390/hydrology8030117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on the Streamflow Modulated by Changes in Precipitation and Temperature in the North Latitude Watershed of Nepal

Abstract: It is unambiguous that climate change alters the intensity and frequency of precipitation and temperature distribution at the global and local levels. The rate of change in temperature in the northern latitudes is higher than the worldwide average. The annual distribution of precipitation over the Himalayas in the northern latitudes shows substantial spatial and temporal heterogeneity. Precipitation and temperature are the major driving factors that impact the streamflow and water availability in the basin, il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The regional climate projections have been produced within the CORDEX‐South Asia initiative (Jones et al ., 2011) Three regional climate models, CNRM‐CM5‐CCAM (CNRM), ACCESS1‐CCAM (ACCESS) and MPI‐ESM‐LR‐CSIRO‐CCAM, were found to be suitable for the mountainous catchment and were selected based on previous research (McGregor, 2005; Aryal et al ., 2019; Bhatta et al ., 2020; Shrestha et al ., 2020; 2021; Maharjan et al ., 2021). The results of a model intercomparison project showed that CCAM is a good model for reproducing the climatic features of Southeast Asia (Fu et al ., 2005).…”
Section: Study Area and Data Usedmentioning
confidence: 99%
“…The regional climate projections have been produced within the CORDEX‐South Asia initiative (Jones et al ., 2011) Three regional climate models, CNRM‐CM5‐CCAM (CNRM), ACCESS1‐CCAM (ACCESS) and MPI‐ESM‐LR‐CSIRO‐CCAM, were found to be suitable for the mountainous catchment and were selected based on previous research (McGregor, 2005; Aryal et al ., 2019; Bhatta et al ., 2020; Shrestha et al ., 2020; 2021; Maharjan et al ., 2021). The results of a model intercomparison project showed that CCAM is a good model for reproducing the climatic features of Southeast Asia (Fu et al ., 2005).…”
Section: Study Area and Data Usedmentioning
confidence: 99%
“…Since the 1960s, water scarcity has grown to a great extent, and the proportion of the world's population living under chronic water scarcity (<1000 m 3 /per capita/year) rose from 9% (280 million people) in 1960 to 35% (2.3 billion) in 2005 [1]. Climate change also exacerbates this problem by changing precipitation and evaporation patterns, which in turn modify freshwater resources collected from rivers and aquifers [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The wavelet spectral analysis for unevenly sampled time series was proposed in the northwestern Mediterranean basin [7]. To analyse the potential impact of climate change on the streamflow in a river basin located in the northern latitude of Nepal, the Soil and Water Assessment Tool (SWAT) hydrological model was used [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the water discharge increase rate observed for 2001-2017 was adopted in the computation based on extrapolation until the projected year 2050. An alternative way to assess the projection and changes in meteorological factors and streamflow, including water yield, is to use specific climate models under different emission scenarios [8]. The trend analysis of the average annual temperature at the weather stations for the period of parallel observations (1959-2017) demonstrated an unambiguously positive tendency, with an increase of 1-2 • C on average (Figure 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation